2004
DOI: 10.1007/bf03167929
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C among drug users: consensus guidelines on management in general practice

Abstract: GPs have an important role to play in the care of patients at risk of, or infected with, HCV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Criteria for referral were most commonly listed for suspected colorectal cancer[8, 10, 12, 13, 15-20, 22, 23, 25, 27, 28, 30, 31, 33, 35, 36, 38, 40]. Other GI conditions for which some referral criteria were found included suspected upper GI cancer[9, 24, 25, 27-30, 38, 39], hepatitis[11, 14, 26, 30], and functional disorders such as irritable bowel syndrome, dyspepsia, diarrhoea and constipation[21, 30, 32, 34, 37]. We found four papers on the management of a variety of important GI conditions, but they did not contain criteria for referral: inflammatory bowel disease[42], pancreatitis [43-44] and acute gastrointestinal blood loss[45].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Criteria for referral were most commonly listed for suspected colorectal cancer[8, 10, 12, 13, 15-20, 22, 23, 25, 27, 28, 30, 31, 33, 35, 36, 38, 40]. Other GI conditions for which some referral criteria were found included suspected upper GI cancer[9, 24, 25, 27-30, 38, 39], hepatitis[11, 14, 26, 30], and functional disorders such as irritable bowel syndrome, dyspepsia, diarrhoea and constipation[21, 30, 32, 34, 37]. We found four papers on the management of a variety of important GI conditions, but they did not contain criteria for referral: inflammatory bowel disease[42], pancreatitis [43-44] and acute gastrointestinal blood loss[45].…”
Section: Resultsmentioning
confidence: 99%
“…More recently, the Dublin Area Hepatitis C Initiative Group created criteria to help predict which patients with hepatitis C from drug use would benefit from therapy [11]. These criteria include HCV and PCR/phenotype testing, clinical and laboratory evaluation of liver status, freedom from unstable drug use, psychiatric history and social stability.…”
Section: Resultsmentioning
confidence: 99%
“…In the same year, a research lead initiative developed consensus guidelines on HCV management in general practice [ 67 ]. The effectiveness of these guidelines was later evaluated in a cluster randomised trial and were found to improve the uptake of screening in practices where the policy was implemented (OR = 3.76 CI = 1.3–11.3) [ 56 ].…”
Section: Epidemiology (32)mentioning
confidence: 99%